2017
DOI: 10.1038/s41598-017-05680-8
|View full text |Cite
|
Sign up to set email alerts
|

DGKδ triggers endoplasmic reticulum release of IFT88-containing vesicles destined for the assembly of primary cilia

Abstract: The morphogenic factor Sonic hedgehog (Shh) signals through the primary cilium, which relies on intraflagellar transport to maintain its structural integrity and function. However, the process by which protein and lipid cargos are delivered to the primary cilium from their sites of synthesis still remains poorly characterized. Here, we report that diacylglycerol kinase δ (DGKδ), a residential lipid kinase in the endoplasmic reticulum, triggers the release of IFT88-containing vesicles from the ER exit sites (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…For example, one of the first identified ciliopathies is the result of a mutation in the gene Ift88/Polaris . Ift88 is a protein that is transported within ciliary vesicles to facilitate ciliary biogenesis [4,5]. Loss of Ift88 leads to cystic kidney disease in both mouse and human [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the first identified ciliopathies is the result of a mutation in the gene Ift88/Polaris . Ift88 is a protein that is transported within ciliary vesicles to facilitate ciliary biogenesis [4,5]. Loss of Ift88 leads to cystic kidney disease in both mouse and human [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…WDR35 did not localize in the Golgi (data not shown). Ding et al () reported that IFT88, a primary cilium protein, localizes in the ER and plays roles in the movement of IFT88‐containing COPII vesicles from the ER exit sites to primary cilia (Ding et al, ). Thus, we determined whether WDR35 was also localized in the ER.…”
Section: Resultsmentioning
confidence: 99%
“…Because vesicles are involved in cilium biogenesis, localization studies were carried out to determine whether Daam1 puncta are vesicles that carry ciliary components. A mCherry-Daam1 construct was co-transfected with an IFT88-GFP construct (Ding et al , 2017). Daam1 localizes to vesicles that carry IFT88 (Figure 4B, S1C).…”
Section: Resultsmentioning
confidence: 99%
“…Although ciliopathies can manifest in a number of different ways, the vast majority of ciliopathies result in kidney abnormalities (Arts and Knoers, 2013). For example, one of the first described ciliopathies is the result of a mutation in the gene IFT88 / Polaris, a protein is transported within vesicles to facilitate ciliary biogenesis (Yoder et al , 2002; Ding et al , 2017). Loss of IFT88 leads to cystic kidney disease in both mouse and human (Moyer et al , 1994; Onuchic et al , 1995).…”
Section: Introductionmentioning
confidence: 99%